İSLAM MİRAS HUKUKUNDA TERİKE TAKSİMİNDE GÖZETİLEN MASLAHATLAR - ARSLAN, HAMZA (Fırat Üniveristesi, 2009)
Bu çalışma, İslam miras hukukunda terikenin mirasçılar arasında taksimi yapılırken gözetilen maslahatları, gaye ve amaçları araştırmak üzere gerçekleştirilmiştir. Zira İslam hukukunda hükümler bir takım gaye ve hedeflere binaen ortaya konmuştur.İslam hukukunda mirasın vârislere dağıtılması hususunda adalet prensibi gözetilerek ölene olan yakınlık, mala duyulan ihtiyaç, akrabalık bağlarının güçlendirilmesi ve toplumda servetin yaygınlaştırılması esas alınmıştır.İslam miras hukukunda miras paylaştırılırken; vârislerin yüklendiği sorumluluklar, miras bırakana faydalı olma, dostluk ve yardımlaşma gibi hususlar da göz önünde bulundurulmuştur. Bu şekilde yapılan paylaştırma hem mûris (miras bırakan) hem de vârisler açısından arzu edilen, tatmin edici bir durum olarak ortaya çıkmaktadır.

This study had been written to investigate the purposes and aims of Islamic inheritance law when the inheritance is shared among the inheritors. However the laws of Islamic law which are regulated according to some of the purposes and aims.The rule of justice is very important about sharing inheritance among inheritors and this sharement is based upon to be a relative of dead person, needs to the merchandise, to get power for the relations of relatives, and also to spread the wealth.It is considered in Islamic law of inheritance during the sharement of inheritance, responsibilities of inheritors which they have to do, to be most usefull one for the deceased person, fellowship and assistance. The sharement like this is a desired and satisfacted case for the respect of deceased person and inheritors.
The guarded benefits about sharing inheritance in Islamic Law
Keywords: Hukuk; Din